FACTORS OF IMPROVING THE PROCESS OF STUDYING GRAPHIC DISCIPLINE WITH THE USE OF EDUCATIONAL CONTROL PROGRAMS (Pedagogy of Higher and Secondary Education, 2008)
The given article exposes the specific of the use of the educational-supervisory programs, in particular at the study of graphic disciplines. Considered problems of introduction of the educational-supervisory programs in an educational process and credible ways of their decision.